Effects of Banditry on Food Production on Borno South Senatorial District - Tanko Shawulu Paul Dominic; Adamu Sadiq; Ado Ibrahim Ahmed (Jurnal Restorasi : Hukum dan Politik, 2025)
Banditry is the formation of armed bands with the intent of attacking state or societal institutions, businesses, or individuals. These are gangs of criminals who terrorize and take valuable possessions of the local populations and travelers, such as their merchandise, money, livestock, camels, and sheep. There are various types of armed banditry. These include social, rural-urban frontier, countryside, mercenary, organized, maritime, and petty banditry. Relative deprivation, social inequalities, and grievances often trigger armed banditry. Accordingly, armed bandits often operate in rural settings, such that their attacks, kidnappings, and cattle rustlings, lootings, among other criminal activities, are carried out in, from and against villages. Their operational control can therefore revolve around rural and border communities, and uninhabited or less populated spots along major roads or waterways. In this manner, the primary victims of armed banditry are innocent citizens residing in or travelling along remote parts of the country. Frustration aggression theory was used. The research used both primary and secondary data. Relative deprivation theory was adopted. The research revealed that banditry led to food insecurity, banditry also led to loss of lives and properties. The research recommend investment on poverty alleviation and also agricultural infrastructure so as to improve food security.